Creating Engagement in Argumentative Writing: A Case of Dialogic Approach to Feedback - Yeni Latipah, - (2021)
Numerous studies have confirmed that the concept of engagement serves as a discourse-semantic resources that is significant in determining the quality of argumentative writing. Unfortunately, little comprehensive understanding could be gained on how to facilitate effective pedagogical approach to support students in constructing engagement in their argumentative writing. This study reported a pedagogical practice of using dialogic feedback in an online group platform to foster the establishment of engagement in argumentative writing. This study followed qualitative case study with multiple data sources including the records of online discussion, students' argumentative text, interview, and observation. The data were analyzed by employing the framework of dialogic feedback (Steen-Utheim & Wittek, 2017) and engagement features (Martin & White, 2005). The findings reveal that in facilitating dialogic feedback, the participating teacher explicitly taught the engagement strategies by applying the procedure and the interactional features of the approach that made the dialogic feedback practice positively perceived by the participants as a meaningful activity in constructing engagement in writing an argumentative text. Although there were various uptakes of engagement resources in the students' text, the students showed progressive development in deploying the engagement sources effectively in their writing.